Saccharomyces cerevisiae Mixed Culture of Blackberry (Rubus ulmifolius L.) Juice: Synergism in the Aroma Compounds Production - Pedro Ulises Bautista-Rosales; Juan Arturo Ragazzo-Sánchez; Gabriela Ruiz-Montañez; Rosa Isela Ortiz-Basurto; Guadalupe Luna-Solano; Montserrat Calderón-Santoyo (The Scientific World Journal, 2014)
Blackberry (Rubus sp.) juice was fermented using four different strains of Saccharomyces cerevisiae (Vitilevure-CM4457, Enoferm-T306, ICV-K1, and Greroche Rhona-L3574) recognized because of their use in the wine industry. A medium alcoholic graduation spirit (<6GL°) with potential to be produced at an industrial scale was obtained. Alcoholic fermentations were performed at 28C°, 200 rpm, and noncontrolled pH. The synergistic effect on the aromatic compounds production during fermentation in mixed culture was compared with those obtained by monoculture and physic mixture of spirits produced in monoculture. The aromatic composition was determined by HS-SPME-GC. The differences in aromatic profile principally rely on the proportions in aromatic compounds and not on the number of those compounds. The multivariance analysis, principal component analysis (PCA), and factorial discriminant analysis (DFA) permit to demonstrate the synergism between the strains.